Determination of Protein and Nitrogen Fractions of Wild Edible Mushrooms - UZUN, YUSUF; GENCCELEP, HUSEYIN; TUNCTURK, YUSUF; DEMIREL, KENAN (Asian Journal of Chemistry, 2010)
The purposes of this study were to determine the crude protein content of mushrooms, as well as the amounts of water soluble nitrogen, trichloro acetic acid soluble nitrogen and phosphotungstic acid soluble nitrogen. Thirty wild edible mushrooms commonly collected in region of Erzurum in Turkey were analyzed for nitrogen contents, crude protein, water soluble-nitrogen (WSN), trichloro acetic acid-soluble nitrogen (TCA-SN) and phosphotungstic acid-soluble nitrogen (PTA-SN). The macronutrient profile in general revealed that the wild mushrooms were rich sources of protein. The investigated mushroom samples contained relatively high total protein content (18.32-64.70 %, based on dry weight). The highest protein concentration were found in Polyporus squamosus (64.70 %, based on dry weight). The highest values of nitrogen fractions was determined as follows: water soluble nitrogen (WSN/TN %) in Marasmius oreades (88.02 %), trichloro acetic acid-soluble nitrogen (TCA-SN/TN %) in Marasmius oreades (78.40 %), phosphotungstic acid-soluble nitrogen (PTA-SN/TN %) Boletus chrysenteron (50.16 %). The average values of total nitrogen, crude protein, water soluble nitrogen, trichloro acetic acid soluble nitrogen and phosphotungstic acid soluble nitrogen of musroom samples were found (5.68, 35.54, 63.45, 53.27 and 31.98 %), respectively. Mushrooms may be a valuable protein supplement for human diets although they are generally preferred for their flavour and taste. Most of the studies on mushroom protein fractions are to be limited on certain mushroom species.